A new Platambus from Sichuan, with new records of species of the P. sawadai group from China (Coleoptera: Dytiscidae: Agabinae) - Hájek, Jiří; Zhang, Tao (Zootaxa, 2019)
Platambus binliui sp. nov. from Sichuan Province, China, is described and illustrated. It belongs to the P. sawadai species group sensu Nilsson (2000). The new species differs from other species of this group by the larger body, punctation of the dorsal surface and shape of male genitalia. New records of members of the P. sawadai group from China are provided: Platambus micropunctatus Nilsson, 2003 (Guangdong), P. punctatipennis Brancucci, 1984 (Fujian, Guangdong, Guizhou, Jiangxi, Zhejiang), P. regulae Brancucci, 1991 (Yunnan), representing a new species for Chinese fauna, and P. wangi Brancucci, 2006 (Hubei). Habitus and median lobe photographs for all mentioned species are provided.